2007
DOI: 10.1007/s00542-007-0478-y
|View full text |Cite
|
Sign up to set email alerts
|

Surface generation analysis in micro end-milling considering the influences of grain

Abstract: The micro end-milling method is a universal micro manufacturing method used to fabricate micro parts and complex 3D micro structures with many materials. Although micrometer size is achieved, their surface quality is not satisfactory. In this paper, the influences of different metal phase grains are researched, and the micro endmilling process is described considering the workpiece with anisotropic properties in micro scope. In this research, the physical characteristics of different grains, specifically frict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 6 publications
0
5
0
1
Order By: Relevance
“…Also, due to the significant variations in the minimum chip thickness over the scan area for the CG sample, the cutting process would be unstable and would result in highly fragmented chips and defects in the machined surfaces. 42 Conversely, the high homogeneity of the UFG Cu samples results in much less variation in the coefficient of friction and hence in the minimum chip thickness over the scanned area. Therefore, the cutting process would be expected to be more stable and the defects on the machined surfaces to decrease.…”
Section: Experimental Set-upmentioning
confidence: 99%
“…Also, due to the significant variations in the minimum chip thickness over the scan area for the CG sample, the cutting process would be unstable and would result in highly fragmented chips and defects in the machined surfaces. 42 Conversely, the high homogeneity of the UFG Cu samples results in much less variation in the coefficient of friction and hence in the minimum chip thickness over the scanned area. Therefore, the cutting process would be expected to be more stable and the defects on the machined surfaces to decrease.…”
Section: Experimental Set-upmentioning
confidence: 99%
“…To analyze the material flow in micro cutting, the stagnation point (S) is considered on the cutting edge of the tool; above this point a chip is formed and below only the elastic-plastic deformation takes place [31,32]. As the undeformed chip thickness (h c ) reduces in micromachining, the positive rake angle of the tool (+γ tool ), shown in Figure 1d [33], is not the actual rake angle participating in the material removal process. The effective rake angle becomes negative (−γ eff ) as the value of UCT (h c ) reaches much smaller than the size of CER (r).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study of conventional longitudinal turning with Mg-Al alloy has shown that feed rate has the most significant impact on surface roughness and machined Figure 1. Schematic of (a) 3D view of orthogonal cutting with single-point cutting tool [28] (b) 2D view of macro machining model [29] (c) 2D view of micromachining model [30] (d) 2D view of ploughing in micromachining [33]. Copyright Permission obtained.…”
Section: Introductionmentioning
confidence: 99%
“…It is characterized by the mechanical interaction between a sharp edged microtool and a workpiece material. Micromilling is similar to macro milling except for the tool size it employs [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%